FACTORS INFLUENCING INFORMATION-SEEKING BEHAVIOUR: A SURVEY OF LITERATURE - Eshak, Erratul Shela; Ahmad, Siti Nurul Akma; Wan Hashim, Wan Nor Syazana (Jurnal ’Ulwan, 2022)
Challenges in information delivery and gaps in knowledge contribute to effective information delivery of either in an academic institution or any other sectors. Seeking information behaviour can help to understand and manage daily operational issues and engage in effectiveness of information delivery. Therefore, this study was conducted to identify the influences that contribute to information-seeking behaviour. The current study involves a reviewed research articles which were gathered from selected Online Databases from the year 2014 to 2022. It was observed that there are various factor influences information seeking behaviour. The identified influencing factors such as innovative behaviour, information need, information sources and personality traits. This paper also helps to understand the conceptual knowledge of information seeking behaviour and its affecting factors in various sector. The debate about factor influences information seeking behaviour is still at its beginnings and it is suggested to promote further investigation on the determinants of such behaviour. In this scenario, we have explored the possible influencing factors affecting information seeking behaviour, which today is a crucial component of successful information literacy skills.